Strategi Meningkatkan Motivasi Belajar Mahasiswa dengan Model Learning Cycle pada Mata Kuliah Sejarah Sastra Indonesia - Titian Gea; R. Kunjana Rahardi; Yuliana Setyaningsih; Pranowo Pranowo (BAHASTRA, 2020)
The study aims to describe a strategy for improving the student learning motivation with a learning cycle model in Indonesian literary subjects. Studies are conducted using qualitative descriptive methods. And then data was collected using observation methods, and interviews. The objective of observation is students' activities in the learning process in the Indonesian literature history class at the sanata dharma university. Interviews were conducted to get some information that was not obtained from observation The data obtained is compiled by deciphering notes, summarizing and selecting data that matches the purpose of the research. Research shows that the learning cycle is one of those strategies to improve the motivation to study in a course on the history of Indonesian literature. Â Â